2021
DOI: 10.15252/embr.202051094
|View full text |Cite|
|
Sign up to set email alerts
|

The Golgi microtubules regulate single cell durotaxis

Abstract: Current understandings on cell motility and directionality rely heavily on accumulated investigations of the adhesion–actin cytoskeleton–actomyosin contractility cycles, while microtubules have been understudied in this context. Durotaxis, the ability of cells to migrate up gradients of substrate stiffness, plays a critical part in development and disease. Here, we identify the pivotal role of Golgi microtubules in durotactic migration of single cells. Using high‐throughput analysis of microtubule plus ends/fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 84 publications
0
24
0
Order By: Relevance
“…Small GTPase RhoA regulates the phosphorylation of myosin light chain (MLC) to promote stress fiber contractility and assembly (Guilluy et al, 2011a,b;Lessey et al, 2012). By using pull-down assay and RhoA-GTP biosensor GFP-AHPH (Piekny and Glotzer, 2008;Rong et al, 2021), we revealed that the active level of GTP bound RhoA significantly decreased in CAV-1 KO cells, exogenously expression of CAV-1-mEGFP restore the active level of RhoA (Figure 3E and Supplementary Figure 3E). To confirm these observations, we tested the consequences downstream of RhoA.…”
Section: Phospho-deficient and Depletion Of Cav-1 Compromises The Assembly Of Contractile Stress Fibers By Deactivating Rhoa-dependent Mymentioning
confidence: 81%
“…Small GTPase RhoA regulates the phosphorylation of myosin light chain (MLC) to promote stress fiber contractility and assembly (Guilluy et al, 2011a,b;Lessey et al, 2012). By using pull-down assay and RhoA-GTP biosensor GFP-AHPH (Piekny and Glotzer, 2008;Rong et al, 2021), we revealed that the active level of GTP bound RhoA significantly decreased in CAV-1 KO cells, exogenously expression of CAV-1-mEGFP restore the active level of RhoA (Figure 3E and Supplementary Figure 3E). To confirm these observations, we tested the consequences downstream of RhoA.…”
Section: Phospho-deficient and Depletion Of Cav-1 Compromises The Assembly Of Contractile Stress Fibers By Deactivating Rhoa-dependent Mymentioning
confidence: 81%
“…While the Golgi localizes to the viroplasm, the Golgi MTOC is not significantly involved in virus production. However, the Golgi MTOC might impact cellular activities of infected cells such as polarized cell migration and secretion, functions that are linked to the Golgi MTOC [ 34 , 35 , 36 , 39 , 40 , 41 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Furthermore, while the loss of the toroid core does not apparently affect virus production, the Golgi together with the centrosome are closely associated with the core, and this configuration may support virus proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the centrosome, non-centrosomal MTOCs (ncMTOCs) organize MTs at various sites in the cell to support a range of cellular functions [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The Golgi apparatus is the predominant ncMTOC in many mammalian cells and requires AKAP450, encoded by AKAP9 , for its MTOC function in mammalian cells, and the Golgi MTOC regulates polarized cell migration and secretion [ 34 , 35 , 36 , 39 , 40 , 41 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In the absence of the centrosome and the Golgi MTOC in mammalian cells, cytoplasmic complexes comprised of PCM proteins including pericentrin and gamma-tubulin generate MTs [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, studies have demonstrated that stiffness-directed migration of cells is essential during development and morphogenesis (Thompson et al, 2019; Shellard and Mayor, 2021), immune response (Bollmann et al, 2015), fibrosis (Liu et al, 2010), and cancer progression (McKenzie et al, 2018; DuChez et al, 2019), where cells migrate through diverse mechanical environments. Several cellular mechanisms and molecular pathways have been implicated in mechano-sensing during durotaxis such as non-muscle myosin II (NMII) activity (Raab et al, 2012; Sunyer et al, 2016), fluctuating focal adhesions (FAs)(Plotnikov et al, 2012), filopodia-based extensions (Wong et al, 2014), Arp2/3 dependent-lamellipodia (Oakes et al, 2018), asymmetric focal adhesion kinase activity (Lachowski et al, 2018), and the Golgi-derived microtubule regulation of FAs (Rong et al, 2021). However, the ways in which cells effectively integrate such processes and molecular pathways to sense, polarize and directionally navigate along stiffness gradients remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, this system produces a very short gradient region and lacks precise tunability. With the introduction of photopolymerized polyacrylamide gels, more precise control became possible, but the implementation of this approach thus far has involved mechanically moving masks that must be precisely controlled in a non-linear fashion or fixed neutral density filters that limits gradient properties (Sunyer et al, 2016; Evans et al, 2018; DuChez et al, 2019; Rong et al, 2021; Yip et al, 2021). Another approach uses physical stretching or deformation of polyacrylamide gel with glass pipettes attached to micromanipulators near individual cells to induce short distance cell migration (Plotnikov et al, 2012; Svec et al, 2019; Puleo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%